Antenatal Care Services Standart Compliance of Village Midwife in East Java Province - Purwaningsih Purwaningsih; Ni Ketut Alit Armini; Esti Yunitasari; Mira Triharini; Cholicul H (Jurnal Ners, 2013)
Introduction: The high Maternal Mortality Rate (MMR) require attention to implementing improvement programs and improving maternal health. According to data from East Java Health Offi ce AKI during 2009 were 260/100,000 live births. Indicators of maternal monitoring imple can be seen from figure K1 coverage (visit pregnant women in the first pregnancy) and K4 (contact at least 4 times during pregnancy for antenatal care).Methods: This study was conducted with the observational design of the “cross-sectional”, is a study to learn the dynamics of the correlation between risk factors with effects, with the approach, observation or data collection at once at some point (time point approach).Result: Variable associated with compliance standards of village midwives in implementing the ANC in the province of East Java is the level of knowledge (p) = 0.014 and the infrastructure required to ANC (p) = 0.000. Other variables did not show a significant relationship such as: age (p) = 0.121, status (p) = 0.831, period of employment (p) = 0.147, education (p) = 0.153, training (p) = 0.664, motivation (p) = 0.525, supervision (p) = 0.887, and rewards (p) = 0.663.Discussion: District Health Office/City should do a refresher on antenatal care in midwife needs to be done, since there are those who have a suffi cient level of knowledge and less. Facilities and infrastructure that support the implementation of Antenatal Care (ANC) should be facilitated effectively, to support midwives performance in implementing standards of care Antenatal Care.